2019
DOI: 10.3390/ijms20081944
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Single Doses of Bonito Fish Peptides and Vitamin D on Whole Blood Gene Expression Levels: A Randomized Controlled Trial

Abstract: Fish contains high quality proteins and essential nutrients including 25-hydroxyvitamin D (25(OH)D). Fish peptide consumption can lower cardiovascular disease (CVD) risk factors, and studies have shown an association between 25(OH)D deficiency, CVD and CVD risk factors, such as diabetes. This study investigated acute effects of a single dose of cholecalciferol (VitD3), bonito fish peptide hydrolysate (BPH), or a combination of both on CVD risk factors and whole blood gene expression levels. A randomized, cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…There is a growing number of indications that sex is an additional, crucial non-environmental factor regulating the level and effect of vitamin D (5,8,25,27,(35)(36)(37)(38) . To date, a number of studies have been carried out in which vitamin D levels have differed between women and men, most of them defining the female sex as being more vulnerable to vitamin D deficiency (5,7,33) .…”
Section: Sources Of Vitamin D and Factors Affecting Its Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing number of indications that sex is an additional, crucial non-environmental factor regulating the level and effect of vitamin D (5,8,25,27,(35)(36)(37)(38) . To date, a number of studies have been carried out in which vitamin D levels have differed between women and men, most of them defining the female sex as being more vulnerable to vitamin D deficiency (5,7,33) .…”
Section: Sources Of Vitamin D and Factors Affecting Its Synthesismentioning
confidence: 99%
“…A clinical study in rats also established that the occurrence of heart disease is associated with low levels of vitamin D, which suggests the usefulness of vitamin D supplementation in treating heart failure (82) . Moreover, a recent study showed that even short-term use of vitamin D affects the expression of genes associated with CVD (37) .…”
Section: Cardiovascular and Cardiometabolic Disordersmentioning
confidence: 99%
“…The effect of a single nutrient, in this case one dose of cholecalciferol (1000 IU), on whole blood gene expression levels was explored in 22 adults. The results showed that this vitamin modulated the expression of the solute carrier family 25 member 20, the gene involved in fatty acid oxidation, various transcription factors, and the genes related to glucose metabolism [ 3 ].…”
mentioning
confidence: 99%